2013
DOI: 10.1371/journal.ppat.1003666
|View full text |Cite
|
Sign up to set email alerts
|

Ehrlichia chaffeensis Uses Its Surface Protein EtpE to Bind GPI-Anchored Protein DNase X and Trigger Entry into Mammalian Cells

Abstract: Ehrlichia chaffeensis, an obligatory intracellular rickettsial pathogen, enters and replicates in monocytes/macrophages and several non-phagocytic cells. E. chaffeensis entry into mammalian cells is essential not only for causing the emerging zoonosis, human monocytic ehrlichiosis, but also for its survival. It remains unclear if E. chaffeensis has evolved a specific surface protein that functions as an ‘invasin’ to mediate its entry. We report a novel entry triggering protein of Ehrlichia, EtpE that functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
89
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(91 citation statements)
references
References 58 publications
(82 reference statements)
1
89
1
Order By: Relevance
“…These domains associated with internalization were not examined in other TRPs but are predicted to be similar. Notably, another study reported that E. chaffeensis uses its surface protein EtpE to bind GPI-anchored protein DNase X to trigger entry via CD147 and hnRNP-K recruitment and actin mobilization (74,75). The domains in TRPs responsible for internalization are structurally distinct from EtpE and are not predicted to interact with DNase X.…”
Section: Discussionmentioning
confidence: 99%
“…These domains associated with internalization were not examined in other TRPs but are predicted to be similar. Notably, another study reported that E. chaffeensis uses its surface protein EtpE to bind GPI-anchored protein DNase X to trigger entry via CD147 and hnRNP-K recruitment and actin mobilization (74,75). The domains in TRPs responsible for internalization are structurally distinct from EtpE and are not predicted to interact with DNase X.…”
Section: Discussionmentioning
confidence: 99%
“…, Mohan Kumar et al. ). The Sca proteins are highly conserved among members of the Rickettsiales, suggesting an important functional role in the adhesion and/or invasion in these bacteria (Blanc et al.…”
Section: Discussionmentioning
confidence: 99%
“…, Mohan Kumar et al. ). BLAST analyses of M. viride and its rickettisal symbiont transcriptomes against these surface proteins revealed the presence of homologs to ku70 and rompB ( sca5 ), suggesting that the bacterial entry into the alga is mediated by the binding of the rickettsial rOmpB to the algal Ku70.…”
Section: Discussionmentioning
confidence: 99%
“…Of remaining ORFs, ∼60 ORFs of the HF strain are likely required for macrophage infection, as orthologs of E. chaffeensis are essential for infection of macrophages including type IV secretion system apparatus (23 ORFs) and effector proteins (3), two-component regulatory system (6), and outer membrane proteins (porin, lipoproteins, invasin; ∼30 ORFs) etc. (Kumagai et al, 2006(Kumagai et al, , 2008Huang et al, 2008;Mohan Kumar et al, 2013;Rikihisa, 2015Rikihisa, , 2017Lin et al, 2016;Sharma et al, 2017;Teymournejad et al, 2017;Yan et al, 2018). Of the remaining ∼330 genes, most encode hypothetical proteins or proteins with unknown functions.…”
Section: Discussionmentioning
confidence: 99%
“…No known pathogen-associated molecular patterns (PAMPs) including endotoxin, peptidoglycan, flagella, common pili, or exotoxin has been detected in Ehrlichia spp., yet they induce acute and/or chronic inflammatory cytokines production in MyD88-dependent, but Toll-like receptors (TLR)-independent manner (Koh et al, 2010;Miura et al, 2011;Rikihisa, 2015). Several virulence factors of E. chaffeensis, which are required for bacterial entry, survival and proliferation of macrophages, have been demonstrated, including ehrlichial invasin that binds host cell receptor and triggers its entry into host cells, three type IV secretion system effectors, three pairs of two-component regulatory system, and outer membrane porins for nutrient acquisition (Kumagai et al, 2006(Kumagai et al, , 2008Mohan Kumar et al, 2013;Rikihisa, 2015Rikihisa, , 2017Lin et al, 2016;Sharma et al, 2017;Teymournejad et al, 2017;Yan et al, 2018). However, whether Ehrlichia spp.…”
Section: Introductionmentioning
confidence: 99%